PARCEL LOCKERS LOCATION AND ROUTING PROBLEM: A BIBLIOMETRIC, DESCRIPTIVE, AND CONTENT ANALYSIS OF EXISTING STUDIES - Akdoğan, Kutay; Özceylan, Eren (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Parcel lockers and collection and delivery points are not new concepts and are recognized by many firms; however, they are not broadly utilized worldwide. The employment of this concept can provide a solution to failed deliveries. In this study, parcel lockers and similar concepts are reviewed quantitatively and analytically. Parcel lockers have been widely studied; however, quantitative approaches are lacking. Therefore, mathematical models, spatial analysis, optimization, and simulation studies on location and routing problems have been extensively examined. This study aims to indicate the current state and future directions. After a rigorous elimination process in the Scopus database, 72 papers were reviewed, and descriptive, bibliometric, and content analyses were performed. This study shows that parcel lockers and collection and delivery points offer various advantages as solutions to last-mile delivery problems, such as regulating traffic congestion, reducing faulty deliveries and the resulting costs, and increasing consolidation.